2009
DOI: 10.1371/journal.pone.0005702
|View full text |Cite
|
Sign up to set email alerts
|

CD152 (CTLA-4) Determines CD4 T Cell Migration In Vitro and In Vivo

Abstract: BackgroundMigration of antigen-experienced T cells to secondary lymphoid organs and the site of antigenic-challenge is a mandatory prerequisite for the precise functioning of adaptive immune responses. The surface molecule CD152 (CTLA-4) is mostly considered as a negative regulator of T cell activation during immune responses. It is currently unknown whether CD152 can also influence chemokine-driven T cell migration.Methodology/Principal FindingsWe analyzed the consequences of CD152 signaling on Th cell migrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
36
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 55 publications
0
36
0
Order By: Relevance
“…8,21,22 The effect on motility and migration has now been reported by several other groups. [25][26][27] In this study, we reveal a clear difference in CTLA-4 modulation of the contact times and motility of Tconvs relative to Tregs. This was shown in several assays including the finding that CTLA-4 ligation reversed the anti-CD3 induced stop-signal on FoxP3-negative cells at concentrations that had no effect on FoxP3-positive Tregs, and that the presence of CTLA-4 reduced the contact times of DO11.10 x CD4 ϩ CD25 Ϫ Tconvs, but not DO11.10 x CD4 ϩ CD25 ϩ Tregs, with OVA presenting DCs in lymph nodes.…”
mentioning
confidence: 53%
See 1 more Smart Citation
“…8,21,22 The effect on motility and migration has now been reported by several other groups. [25][26][27] In this study, we reveal a clear difference in CTLA-4 modulation of the contact times and motility of Tconvs relative to Tregs. This was shown in several assays including the finding that CTLA-4 ligation reversed the anti-CD3 induced stop-signal on FoxP3-negative cells at concentrations that had no effect on FoxP3-positive Tregs, and that the presence of CTLA-4 reduced the contact times of DO11.10 x CD4 ϩ CD25 Ϫ Tconvs, but not DO11.10 x CD4 ϩ CD25 ϩ Tregs, with OVA presenting DCs in lymph nodes.…”
mentioning
confidence: 53%
“…8,21,22 Reduced contact times by CTLA-4 would be expected to limit TCR ligation events and raise the threshold for T-cell activation. [21][22][23][24] The motility inducing effects of CTLA-4 have been confirmed by several laboratories in various in vivo models, [25][26][27] and involves CTLA-4 activation of the GTP binding protein Rap1 and LFA-1 adhesion. 24,28 Immune responses are regulated by a balance of inflammatory responses by conventional or responder T cells (Tconvs) and suppression by Tregs that maintain tolerance to self-antigen.…”
mentioning
confidence: 86%
“…Absence of CTLA-4 engagement during Ag priming leads to enhanced cytokine production (18)(19)(20). Moreover, CTLA-4 recently has been shown to mediate resistance to apoptosis in vitro, to enhance migration of CD4 + T cells in vivo (21)(22)(23)(24)(25), and to be constitutively expressed on natural regulatory T cells (nTregs) (26). Importantly, the suppressive function of nTregs is dependent on CTLA-4, which impedes activation of Ag-experienced T cells via downregulation of CD80 and CD86 on dendritic cells and induces the tryptophan catabolizing enzyme IDO (27)(28)(29).…”
Section: Activation and Subsequent Differentiation Of Naive Cd4mentioning
confidence: 99%
“…We have shown that CTLA-4 facilitates critical functions of already activated T-lymphocytes: Suppression of T-cell proliferation [4] , suppression of effector functions [20,21] , induction of survival [10] and migration of T-lymphocytes [23] . Lymphocytes that receive a CTLA-4 signal are stopped in their proliferation and survive [1] .…”
Section: Ctla-4 In the Differentiation Of T-lymphocytesmentioning
confidence: 98%
“…This ensures that the immune response is stopped. In addition, T-lymphocytes that receive a CTLA-4 signal migrate along inflammatory and homeostatic chemokine gradients [23,11] . The lymphocytes surviving at the end of an immune response and migrating to memory areas might be potential precursors of memory cells.…”
Section: Ctla-4 In the Differentiation Of T-lymphocytesmentioning
confidence: 99%